Slip Effects on Unsteady Free Convective Heat and Mass Transfer Flow with Newtonian Heating - Hussanan, Abid; Khan, Ilyas; Mohd Zuki, Salleh; Sharidan, Shafie (VINČA Institute of Nuclear Sciences, 2016)
This article investigates the effects of slip condition on free convection flow of viscous incompressible fluid past an oscillating vertical plate with Newtonian heating and constant mass diffusion. The governing equations together with imposed initial and boundary conditions are solved using the Laplace transform technique. The results for velocity, temperature and concentration are obtained and plotted for the embedded parameters. The results for skin friction, Nusselt number and Sherwood number are computed in table. It is investigated that the presence of slip parameter reduces the fluid velocity.